Impact of Authoritative Parenting Style on Self-Esteem and Resilience Among Undergraduate Students (Journal of Asian Development Studies, 2024)
The aims of undertaking the following research have to assess the relationship between authoritative parenting and self-esteem as well as the levels of resilience among undergraduate students. According to this research, the authoritative style of parenting has a positive relation to self-esteem and resilience as two interrelated factors. For this study, a sample of 250 undergraduate students from AWKUM was used and research techniques like descriptive analysis and Pearson correlation coefficients. The results indicate a significant positive correlation between authoritative parenting and resilience (r = .638, p < .01), as well as between authoritative parenting and self-esteem (r = .664, p < .01). Furthermore, a strong correlation was observed between resilience and self-esteem (r = .934, p < .01). These findings highlight the importance of authoritative parenting in promoting psychological well-being among undergraduate students.